SERVQUAL scale for quality measurement: a case study in a company of public transport - Silva, Deoclécio Junior Cardoso da; Godoy, Leoni Pentiado; Godoy, Taís Pentiado; Wegner, Roger da Silva; Sudati, Lucas Urach (Revista de Administração da UFSM, 2019)
Various services provided throughout the country in recent years, generated skilled jobs, increased internal and external competitiveness and accelerate innovation. It has expanded customer choice, preferring companies that offer differentiated services that meet their needs. Therefore, the aim of this study was to establish a measurement of services using SERVQUAL, and five dimensions of quality. It is evident in the public transport company, factors that must improve more efficiently and effectively what customers need and expect of the services received. The methodology was characterized as descriptive as it described the quality and measurement of SERVQUAL guidelines, when dealing with a case study because it involves a single company. In the analysis of results, it was used descriptive statistics and SERVQUAL scale with five dimensions of quality, taking into account the importance of each issue. The issue that stood out was the guarantee, reaching the ideal quality, both in expectancy and experience. It is suggested for future studies, management for an implementation project of the SERVQUAL methodology for continuous measurement of quality enterprise.